Extrusion and injection moulding induced degradation of date palm fibre - polypropylene composites. (August 2021) - Domenek, Sandra; Berzin, Françoise; Ducruet, Violette; Plessis, Cédric; Dhakal, Hom; Richaud, Emmanuel; Beaugrand, Johnny
Highlights: Date palm fibres increase tensile modulus of injected PP composites. GC-MS analysis and attribution of main VOCs causing odour of biocomposites. VOC generation takes place mainly during injection process. Abstract : The use of date palm fibres, which are an abundant by-product of agriculture, as natural reinforcement in polypropylene (PP) was studied. Because odour emissions are one of the major challenges for natural fibre-based composites, the emission of Volatile Organic Compounds (VOC) generated at different processing steps was analysed online. The severest degradation on the date palm fibre morphology was observed at the injection moulding step, but even when degradation occurred date palm fibres were an effective reinforcement of PP and increased the Young's modulus significantly. Generation of odorous compounds caused by thermal degradation of date palm fibres such as furfural alcohol or methyl furfural was astonishingly low during the twin-screw extrusion and granulation process. In coherence with the evolution of the fibre morphology, the most critical processing step was the injection process. In conclusion, date palm fibres are a promising natural fibre for the production of natural fibre-based composites. Adapted twin-screw extrusion conditions allow for minimizing VOC emissions, but particular attention needs to be given to the optimization of the injection process.